Reducing supply risk caused by the stockwhip effect in supply chains - Jeeva, Ananda (IEOM Research Solutions Pty Ltd, 2011)
To enhance today's supplier relationship management, it requires collaborative relationship information especially supplier's capability intelligence. Intimate knowledge about the supply network leads to the collective synergy to overcome supply uncertainties. Incompatible relationships create supply risk caused by the stockwhip effect. The challenge to procurement managers is to ensure that there are no supply disruptions. This paper investigates and proposes a conceptual model for reducing supply risk caused by 'stockwhip effect'. Stockwhip effect is the domino effect of constraints in the higher order supplier network. This conceptual model lays the foundation for future action research in better mitigation of supply risk.